2023
DOI: 10.1371/journal.pone.0290696
|View full text |Cite
|
Sign up to set email alerts
|

Ephedrine and pseudoephedrine in Ephedra saxatilis on the vertical altitude gradient changed in southern Tibet Plateau, China

Mengnan Lu,
Yongjuan Zhang,
Shiyan Wang
et al.

Abstract: Ephedra is one of the world’s most important plants, used in medicine, plants and ecology. Most Ephedra grows in plain areas and is stable. But the plateau environment is special, with the change of altitude, the variety difference of plateau Ephedra saxatilis is very obvious. E. saxatilis metabolism on the Tibetan Plateau is not only affected by altitude, but also environmental conditions such as climate conditions and different soil components. However, the change mechanism of E. saxatilis alkaloids in speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Their content varies from one Ephedra species to another, depending on diverse plant growth parameters, such as altitude. It has been observed recently with another species (Ephedra saxatilis) that the ephedrine content increased as the altitude gradient increased, and pseudoephedrine decreased as the altitude gradient decreased [171]. There is also a seasonal variation of the alkaloid content [161].…”
Section: Discussionmentioning
confidence: 91%
“…Their content varies from one Ephedra species to another, depending on diverse plant growth parameters, such as altitude. It has been observed recently with another species (Ephedra saxatilis) that the ephedrine content increased as the altitude gradient increased, and pseudoephedrine decreased as the altitude gradient decreased [171]. There is also a seasonal variation of the alkaloid content [161].…”
Section: Discussionmentioning
confidence: 91%
“…For methylephedrine content, higher levels are observed in XZ, NMG, SL, SX, WQC, WQM, and WQZ, indicating greater levels in Ephedra from higher altitude areas. Consequently, it is hypothesized that the content of ephedrine, pseudoephedrine, and alkaloids increases with altitude gradient ( Kitani et al., 2009 ; Guo et al., 2022 ; Lu et al., 2023 ), as illustrated in Supplementary Figures S6 and S7 .…”
Section: Discussionmentioning
confidence: 99%
“…Geographically, it has been observed that the total alkaloid content of E. sinica and E. equisetina in eastern and central Mongolia is 1.43% higher than that in Ephedra from other regions ( Kitani et al., 2009 ). Additionally, ephedrine levels increase with altitude, while pseudoephedrine levels decrease with altitude ( Lu et al., 2023 ). Thus, variations in the contents and proportions of primary and secondary metabolites among different regions and species of Ephedra reflect differences in their metabolic activities ( Loera et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…For methylephedrine content, higher levels are observed in XZ, NMG, SL, SX, WQC, WQM, and WQZ, indicating greater levels in Ephedra from higher altitude areas. Consequently, it is hypothesized that the content of ephedrine, pseudoephedrine, and alkaloids increases with altitude gradient (Kitani et al, 2009;Guo et al, 2022;Lu et al, 2023), as illustrated in Supplementary Figures S6 and S7.…”
Section: Discussionmentioning
confidence: 99%